The electrochemical synthesis of europium boride - Bukatova G.A.; Kuznetsov S.A.; Gaune-Escard M. (Journal of Mining and Metallurgy. Section B: Metallurgy)
The electroreduction of boron, europium and the electrochemical synthesis of europium boride have been investigated in NaCl-KCl-NaF(10 wt. %) melt on silver and molybdenum electrodes. The parameters of boron reduction in the chloride-fluoride melt have been obtained and the character of its joint deposition with europium has been studied.